Fault lines : fractured families and how to mend them - Pillemer, Karl A. (Avery, an imprint of Penguin Random House LLC, 2020)
"Estrangement from a family member is one of the most painful life experiences. It is devastating not only to the individuals directly involved--collateral damage can extend upward, downward, and across generations, More than 65 million Americans suffer such rifts, yet little guidance exists on how to cope with and overcome them. In this book, Karl Pillemer combines the advice of people who have successfully reconciled with powerful insights from social science research. The result is a unique guide to mending fractured families. Fault Lines shares for the first time findings from Dr. Pillemer's ten-year groundbreaking Cornell Reconciliation Project, based on the first national survey on estrangement; rich, in-depth interviews with hundreds of people who have experienced it; and insights from leading family researchers and therapists. He assures people who are estranged, and those who care about them, that they are not alone and that fissures can be bridged"--